2023
DOI: 10.3389/fphys.2023.1089065
|View full text |Cite
|
Sign up to set email alerts
|

Beneath the cuff: Often overlooked and under-reported blood flow restriction device features and their potential impact on practice—A review of the current state of the research

Abstract: Training with blood flow restriction (BFR) has been shown to be a useful technique to improve muscle hypertrophy, muscle strength and a host of other physiological benefits in both healthy and clinical populations using low intensities [20%–30% 1-repetition maximum (1RM) or <50% maximum oxygen uptake (VO2max)]. However, as BFR training is gaining popularity in both practice and research, there is a lack of awareness for potentially important design characteristics and features associated with BFR cuff a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
0
16
1
Order By: Relevance
“…Our study reported high RPD in both BFR conditions compared to No-BFR with equal RPE. Lastly, our results conflict with a recent study investigating autoregulation of applied pressures using another commercially available BFR training device [26], indicating that acute responses to a BFR training program with autoregulation are possibly device-specific [20].…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study reported high RPD in both BFR conditions compared to No-BFR with equal RPE. Lastly, our results conflict with a recent study investigating autoregulation of applied pressures using another commercially available BFR training device [26], indicating that acute responses to a BFR training program with autoregulation are possibly device-specific [20].…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
“…As BFR becomes more widely implemented in different practice settings [1], the availability of BFR equipment for consumer purchase has increased. However, there is a dearth of research available on the different types of BFR devices used, as well as features marketed to enhance its safety, tolerability, and/or efficacy during application [20]. One of those features is autoregulation of applied BFR pressures, whereby the applied pressure to the exercising limb from the BFR cuff is kept relatively constant compared to a manu-ally inflatable (non-autoregulated) cuff that does not adjust and, therefore, may heighten cardiovascular and perceptual exercise responses [21].…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, the current study is interestingly the first to reliably and consistently assess narrow-elastic cuff AOP; the preponderance of preceding studies utilizing similarly designed Kaatsu bands have operated with a single standardized (i.e., arbitrary) pressure or were unable to dependably determine arterial occlusion amongst all participants [12,13,19,21,[38][39][40][41]. Moreover, employing arbitrary pressures may result in excessive arterial blood flow restriction and subsequently deleterious cardiovascular complications [5][6][7]42]. While these aforementioned investigations rarely exceed prescribed pressures of 300 mmHg, the current study illustrates that four participants reached or exceeded their AOP threshold (as high as 120% AOP) using the cuff manufacturer's arbitrary recommended pressure of 300 mmHg [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Multichambered bladder devices are designed to reduce the potential for full arterial occlusion 7 and are not an appropriate device for integrating the AOP equation as it will likely greatly underestimate the applied pressure given its construction is designed to avoid the potential for such personalization of pressure. 8 Prior research has shown that the multi-chambered bladder system is unable to personalize pressures and has difficulty in modulating resting blood flow-factors that are likely important to inducing some of the beneficial effects of BFR exercise. Citherlet et al 7 showed that femoral blood flow was unaltered from resting conditions with pressures as high as 300 mmHg, a pressure that is almost double to that used in the current study (180 mmHg).…”
mentioning
confidence: 99%
“…Multi-chambered bladder devices are designed to reduce the potential for full arterial occlusion 7 and are not an appropriate device for integrating the AOP equation as it will likely greatly underestimate the applied pressure given its construction is designed to avoid the potential for such personalization of pressure. 8…”
mentioning
confidence: 99%